A moderating affect of leadership on a success of enterprise–wide risk management practices - Ab. Wahab, Norlida; Kasim, Isahak (2012)
﻿This paper addresses the vital role of leadership for a success of Enterprise-Wide Risk Management (EWRM) practices among financial and non-financial companies of Public Listed Companies (PLCs) of service sector in Malaysia. A triangulation approach was adopted to get an enriched data collection and analysis for the study. From a survey on 14 financial companies, 41 non-financial companies and 4 companies in a case study, it is found that support and commitment from leaders are required for an effective implementation of EWRM. This is supported by the result from Hierarchical Multiple Regression analysis which reveals that the leadership support moderates the relationship between EWRM framework and organisational culture on shareholder value. Indeed, the findings from four case study analysis confirmed the crucial role of leadership factors in creating a risk management culture and for a successful EWRM practices.